Kalevala through Translation: Continuity, Rewriting and Appropriation of an Epic - Plourde, Éric (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe Kalevala, the national epic of the Finnish people, published in the 19th century and created by E. Lönnrot from songs collected in the Karelian countryside (Northwestern Russia), is the result of a long process of rewriting. This process has manifested itself through successive retranslations in various languages and through certain strategies favored by the epic’s translators. Recent translations reflect a tendency to appropriate the epic through the use of a vocabulary and poetic style that are specific to the culture of the translator. For example, verse translations in Tamil are structured in the manner of folk epics of Southern India; while in the French verse translation the translator has made abundant use of archaisms and neologisms.